Popia Pisang Cokelat: Inovasi Camilan Kekinian Berbasis Pangan Lokal untuk Meningkatkan Nilai Ekonomis Produk Olahan Pisang - Wahyu Muh. Syata; Muhammad Juwantho Lewa; Murni Nia; Murniati Murniati; Jumatin Jumatin; Hasniah Hasniah; Fitra Ramadani; A. Amaliah (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
he shifting lifestyle of students towards practical and instant snacks often neglects nutritional aspects. This community service activity aims to create an innovative, healthy, and economically valuable banana-based snack called "Popia Pisang" (banana-chocolate spring roll) and to analyze its production process and market potential. The activity was conducted in April 2026 using a structured three-stage method: preparation, production (including banana processing, chocolate melting, filling mixing, wrapping, and storage), and frying/presentation. The results showed that the team successfully produced 30–40 Popia Pisang units in both ready-to-eat and frozen forms. Key technical challenges such as banana oxidation were effectively prevented using lime water, while the addition of cornstarch and cooling of the filling improved dough stability and prevented spring roll wrapper damage. The product achieved a crispy texture with a soft filling, receiving positive preferences from students. Economically, Popia Pisang generates a value-added of approximately 40–50% of production costs, which is competitive compared to other processed banana products (30–45%). The use of local ingredients like Raja banana and premium melted chocolate provided a distinctive taste and melted texture. In conclusion, Popia Pisang has significant potential as a sustainable food business based on local resources, contributing to community empowerment and economic improvement.